2017
DOI: 10.1080/22201181.2017.1281519
|View full text |Cite
|
Sign up to set email alerts
|

Double trouble: hoarseness and Horner’s after supraclavicular brachial plexus block

Abstract: View related articles View Crossmark data Citing articles: 1 View citing articles Southern African Journal of Anaesthesia and Analgesia is co-published by Medpharm Publications, NISC (Pty) Ltd and Informa UK Limited [trading as the Taylor & Francis Group].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…[6][7] Similarly, Balaji et al reported RLN block and Horner's syndrome in a same patient following peripheral nerve stimulator (PNS) guided right supraclavicular block. 8 The RLN block due to left supraclavicular block is very rare. There is only one case report of an RLN block following the left supraclavicular block.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7] Similarly, Balaji et al reported RLN block and Horner's syndrome in a same patient following peripheral nerve stimulator (PNS) guided right supraclavicular block. 8 The RLN block due to left supraclavicular block is very rare. There is only one case report of an RLN block following the left supraclavicular block.…”
Section: Discussionmentioning
confidence: 99%
“…7 When the large volume of LA is injected there is a possibility of proximal spread of drug involving RLN as previously reported. 3,6 Various techniques have been described to limit the spread of injected LA into the brachial plexus. These include the use of tourniquet position of the arm, use of massage, multiple injection techniques and digital pressure.…”
Section: Discussionmentioning
confidence: 99%
“…2 The recurrent laryngeal nerve palsy is an occasional complication mostly reported on the right-sided blocks and one case of left RLN palsy has been reported using USG for SCB. 3,4,5,6 We report a case of a 50-year-oldfemale patient, who developed hoarseness of voice following a left-sided classical supraclavicular block.…”
Section: Introductionmentioning
confidence: 99%
“…Table II). a popular procedure 3 . In recent years it has gained popularity with addition of various adjuncts to local anaesthetic solution in an attempt to increase its e cacy and duration.…”
Section: Introductionmentioning
confidence: 99%